Peran Mahasiswa PPL dalam Mewujudkan Apresiasi Perayaan Isra’ Mi’raj Melalui Media Audiovisual dan Reward Learning - Misbahul Huda; Dwi Aminatus Sa’adah; Endriyanti Familiya Cahyani (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2026)
Religious learning activities in madrasas are often conducted using lectures, which are less engaging for students. This study aims to analyze the role of students in enhancing their appreciation of the Isra' Mi'raj through the use of audiovisual media and reward learning at MI Manbail Futuh Beji Jenu Tuban. The research method used was a descriptive qualitative study, with observation, interviews, and documentation as data collection techniques. The results showed that the use of audiovisual media increased student interest and understanding, while reward learning encouraged active participation in learning. The PPL students acted as facilitators and innovators in creating more engaging learning. In conclusion, this method is effective in enhancing student understanding of religious material and can be an innovative alternative in madrasah learning.